Female Swearing on WhatsApp Communications: A Sociolinguistics Perspective - Fahrisal Kurniawanti; Adam Damanhuri (Jurnal Bahasa dan Sastra, 2022)
Traditionally, swearing was considered a taboo subject. However, in today’s era swearing has become a common thing.  It is practiced not only by men but women also practice it. To avoid social impoliteness, it is practiced in various ways, purposes, and languages based on the context. This research analyzed the types and functions of English swearing used by females on WhatsApp seen from a sociolinguistics perspective. Ljung (2011) and Vingerhoets & Bylsma (2013)’s theories were applied in this research. Observations were conducted through WhatsApp stories in gaining eight written utterances data and virtual interviews were conducted by eight participants in gaining the functions of swearing data. The results show four types of swear words covered the use of swearing, namely: religious theme, scatological theme, sexual activities theme, and mother/family theme. Each of these themes has different functions depending on the context of utterances. Other results indicate that females function English swearing in intra-individual and inter-individual. Intra-individual functions lead to show anger, frustration, and annoyance. Inter-individual functions lead to insulting others and showing solidarity. These functions were triggered by positive emotions (excitement and chill out with friends) and negative emotions (anger, frustration, and annoyance). Mostly Females swear triggered by negative emotions.